Atrial fibrillation and the risk of myocardial infarction: a nation-wide propensity-matched study. Issue 1 (December 2017) - Lee, Hye; Yang, Pil-Sung; Kim, Tae-Hoon; Uhm, Jae-Sun; Pak, Hui-Nam; Lee, Moon-Hyoung; Joung, Boyoung
Abstract In addition to being an established complicating factor for myocardial infarction (MI), recent studies have revealed that atrial fibrillation (AF) increased risk of MI. This study is to evaluate the risk of MI associated with AF in a nationwide population based cohort. We examine the association between AF and incident MI in 497, 366 adults from the Korean National Health Insurance Service database, who were free of AF and MI at baseline. AF group (n = 3, 295) was compared with propensity matched no-AF group (n = 13, 159). Over 4.2 years of follow up, 137 MI events occurred. AF was associated with 3-fold increased risk of MI (HR, 3.1; 95% CI, 2.22–4.37) in both men (HR, 2.91; 95% CI 1.91–4.45) and women (HR, 3.52; 95% CI 2.01–6.17). The risk of AF-associated MI was higher in patients free of hypertension, diabetes, ischemic stroke, and dyslipidemia at baseline. The cumulative incidence of AF-associated MI was lower in patients on anticoagulant and statin therapies. Our finding suggests that AF complications beyond stoke should extend to total mortality to include MI.